Obtenção de scaffolds a base de colágeno e quitosana como biomaterial para liberação de fármaco - Bueno, Mariana Chiocheta (2021)
The present work aims at the use of natural and biocompatible polymers to obtain blends in the form of scaffolds by lyophilization. The polymers used to form the matrices were chitosan, derived from chitin, and collagen extracted from bovine tendon. The drug chosen to test the release capacity of polymeric matrices was ceftriaxone. The following collagen and chitosan mass ratios were evaluated: C25:Q75; C50Q50 and C75:Q25. The chemical interaction between the components for all samples was confirmed by Fourier transform infrared spectroscopy. The addition of chitosan changed the morphological properties in the polymer matrix, observed through SEM, and increased the percentage of porosity, which was between 89 and 91%. The pore diameter measured was between 0.085 and 0.065 mm, above the minimum value for cell fixation. In the kinetic study, the C25:Q75F sample, in Mili-Q water and PBS solvents, showed a lower release rate in 24 hours. For the hemolytic activity test, the biomaterials were not toxic to blood cells. Samples C75:Q25 and C75:Q25F had hemolysis percentage values less than 5%, which is within acceptable limits for tissue engineering applications. In the biological assay, the inhibition halo was present in polymer matrices incorporated with ceftriaxone.